1983-84 ネン ナンキョク マクマードサウンド チイキ ノ チキュウ カガク テキ チョウサ - 松本, 源喜; マツモト, ゲンキ; 鳥居, 鉄也; トリイ, テツヤ; 川野, 田実夫; カワノ, タミオ; 長, 連英; チョウ, ツラヒデ; 小畑, 芳春; コバタ, ヨシハル; Matsumoto, Genki I.; Torii, Tetsuya; et al. (1985)
P(論文) 1983-84年南極夏季のフィールドシーズンに, マクマードサウンド地域に分布する湖沼の地球化学的調査を実施した。テイラー谷のボニー湖およびライト谷のバンダ湖における湖水の物理・化学的特性の鉛直分布は, 従来の観測結果と同様で, かなり安定していることが示された。バンダ湖では天気の良い日の昼(1300-1500)と夜(0100-0300)に水質調査を行い, 昼夜変動の有無を調べたが, 著しい変動は確認できなかった。ライト谷のラビリンスおよびサウスフォーク, ロス島のマクマード基地周辺には, 塩水池を含む多数の池が存在するが, 今回新たに13カ所の池の調査を行った。ラビリンスおよびサウスフォークには, pHが著しく高い池(>10)や溶存酸素が極端に高い池(20-35.0ml/l)が確認された。高いpHは主として藻類の光合成活動によるものであろう。ボニー西湖における水深15m以深の全炭酸濃度(55-69mM)は, 調査した他の湖沼(>0.05-7.5mM)と比較し, 著しく大きくその起源には興味がもたれる。 During the 1983-84 austral summer, Japanese geochemical studies in the Dry Valleys and Ross Island of the McMurdo Sound region in Antarctica were carried out to observe the annual variation of the vertical distribution of physicochemical properties of waters for Lakes Bonney and Vanda, to clarify the changes of water quality of Lake Vanda for day and night, to characterize the physicochemical natures of lakes and ponds in the Labyrinth, South Fork and near Lake Vanda of the Wright Valley and around McMurdo Station of Ross Island, and to determine total carbonate materials (H_2CO_3+HCO^-_3+CO^<2->_3=ΣCO_2) in lake and pond waters. The vertical distribution of physicochemical properties of Lakes Bonney and Vanda was similar to those of previous studies, indicating that the stratification of lake waters is still stable. Any remarkable changes in the vertical distribution of the water quality of Lake Vanda for day and night were not observed. The lakes and ponds in the Labyrinth (18 ponds), South Fork (3), near Lake Vanda (2), and sorroundings of McMurdo Station (2) studied were generally small and thus chlorinity varied considerably during these 10 years. The ponds with high pH values (>10) found in the Labyrinth and South Fork were considered to be mainly attributable to the photosynthetic activity of epibenthic organisms, which are widely distributed there. The ponds with extremely high dissolved oxygen (20-35ml/l) were also found in the Labyrinth as in the case of the surface waters of Lakes Bonney and Joyce in the Dry Valleys. The ...